Inovasi Si Besti: Pemberdayaan Kader Kesehatan untuk Cegah Stunting melalui Daun Kelor - Riansih, Chici; Noor, Ahmad Yani; Seha, Harinto Nur (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: Stunting is a nutritional disorder stemming from chronic undernutrition during the critical first 1000 days of life, a period that holds profound importance for early development. This condition manifests in growth deficiencies in children, leading to a height significantly below the age-appropriate standard. The primary objective of this program was to disseminate comprehensive knowledge regarding the multifaceted benefits of moringa for pregnant women, toddlers, and lactating mothers.. Methodology: This service activity was carried out on 20 July 2024 and 21 October 2024 in Barukan Village, Manisrenggo, Klaten, Central Java. Educational methods and filling out pre-post test questionnaires to determine and assess the level of success of the education carried out. Results: Results: It was found that the average knowledge score before education was in the good category 6 (12%), 16 (32%), 28 (56%). Knowledge after education was obtained in the good category 37 (74%), and sufficient 13 (26%). Conclusions: The innovation of making risol and pudding made from moringa leaves is a promising strategic approach in supporting the prevention of stunting in toddlers. The high nutritional content of moringa leaves as well as an attractive and easily accepted form of preparation for children make this product an applicable nutritional solution. Limitations: Health cadres who participated in this service activity were limited to those who were active in health cadre activities at the posyandu. Contribution: Health cadres play a role in educating the community about the benefits of moringa in preventing stunting. They help the community understand the importance of adequate nutrition, especially for children, how to process moringa leaves   into nutritious food, Health cadres also play a role in monitoring the development of children who receive moringa pudding as part of stunting prevention efforts. improving the knowledge of health cadres.